DOCUMENT ABOUT THE PREPARATION FOR BOOK SCIENCE STUDIES AT VILNIUS UNIVERSITY AND LIBRARY REPLENISHING STRATEGIES IN THE FIRST DECADES OF THE 19TH CENTURY - Navickienė, Aušra; Pacevičius, Arvydas (Knygotyra, 2017)
...